Technological coherence and the adaptive resilience of regional economies - Silvia Rocchetta; Andrea Mina (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2018)
This paper explores the effect of different regional technological profiles on the resilience of regional economies to exogenous shocks. It presents an empirical examination of the determinants of resilience through panel analyses of UK NUTS III level data for the 2004-2012 period. The results indicate that regions endowed with technologically coherent - and not simply diversified - knowledge bases are better prepared to face an unforeseen downturn and display adaptive resilience. Moreover, local economies tend to be more adaptable if they innovate in sectors with the strongest growth opportunities, even though firms' net entry does not appear to contribute significantly towards resilience.
Keywords: O30; R11; O33; 330; resilience; adaptation; innovation; technological variety; financial crisis